Characterization of underground starchy crops as raw materials: carbohydrates, starch, mucilage, and phenolic compounds - Cereda, Marney Pascoli [UNESP]; Pereira, Joelma; Andrade, Luan Alberto (Elsevier, 2022)
The underground organs that store starch, such as roots, tubers, corms, and rhizomes, have between 11% and 40% dry matter, with high starch contents and, for most of them, low fiber, fat, and protein contents, characteristics that make them very different from cereal grains. However, some underground starchy crops, such as cocoyam and several yam varieties, may have higher protein and lipid contents, compounds that could add value to these crops. Others, such as cassava and arrowroot, have fibers with potential market value. Many of these underground starchy crops have accompanying substances such as mucilage and phenolic compounds. Mucilage may hinder starch extraction, and phenolic compounds may interfere with starch color. Further research is needed to understand these phenomena, but the important properties of underground starchy crops may increase their commercial interest.
Keywords: by-products; dry matter; fat; oxalates; Protein